Tropical soils properties and management for sustainable agriculture - Juo, A. S. R. (Oxford University Press, 2003)
1. Introduction. 2. Mineralogy. 3. Soil Chemistry. 4. Soil Physics. 5. Soil Biology and Microbiology. 6. Soil Fertility. 7. Soil Formation and Classification. 8. Major Soils of the Tropics: A Descriptive Classification Based on Clay Mineralogy. 9. Soil Management: An Overview. 10. Properties and Management of Kaolinitic Soils. 11. Properties and Management of Oxidic Soils. 12. Properties and Management of Smectitic Soils. 13. Properties and Management of Allophanic Soils. 14. Soils and Sustainable Agriculture.
Keywords: Soils -- Tropics.; Sustainable agriculture -- Tropics.; Tropics.; Tropen.; elektronické knihy; electronic books